2018
DOI: 10.4103/0973-1482.176423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of accuracy of out-of-field dose calculations by TiGRT treatment planning system in radiotherapy

Abstract: This study highlights the limitations of TiGRT TPSs in calculating of the out-of-field dose. It should be noted that out-of-field data for this TPS should only be applied with a certain understanding of the accuracy of calculated dose outside the treatment field. Therefore, using the TPS-calculated dose could lead to an underestimation of secondary cancer risk as well as a weak clinical decision for patients with implantable cardiac pacemakers or pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
1
20
1
1
Order By: Relevance
“…For outside field regions, the TiGRT TPS underestimated the dose compared to the measured doses by TLD-100. Our results related to out of field regions were consistent to several studies [26][27][28] ; as results of these studies showed that TiGRT TPS underestimated the dose of out-of-field regions for most points.…”
Section: Discussionsupporting
confidence: 92%
“…For outside field regions, the TiGRT TPS underestimated the dose compared to the measured doses by TLD-100. Our results related to out of field regions were consistent to several studies [26][27][28] ; as results of these studies showed that TiGRT TPS underestimated the dose of out-of-field regions for most points.…”
Section: Discussionsupporting
confidence: 92%
“…Morever, their findings demonstrated TPS underestimated dose of the outside field which is mentioned compared to the corresponding measurements. Farhood, et al [15] reported that TiGRT TPS underestimated the out-of-field dose for most points in physical wedged field and the confidence limit value for region was 55.24.…”
Section: Farhood B and Ghorbani Mmentioning
confidence: 98%
“…There are several studies which have quantified the dose calculation accuracy of different TPSs in out-of-field regions [5,[12][13][14][15][16]. In a study, Huang, et al [5] reported that Pinnacle TPS underestimates the out of field dose by an average of 50% for intensity modulated radiation therapy (IMRT) treatment plans and this underestimation is worsened with increasing distance from the edge of treatment field.…”
Section: Farhood B and Ghorbani Mmentioning
confidence: 99%
“…At the same time, there are several published works identifying the poor performance, including under-and over-estimation, of out-of-field dose calculation of specific TPSs 27,28,29 .…”
Section: Accepted Articlementioning
confidence: 99%
“…At the same time, there are several published works identifying the poor performance, including under‐ and over‐estimation, of out‐of‐field dose calculation of specific TPSs. 27 , 28 , 29 However, the accuracy of out‐of‐field dose calculation of the Monaco TPS, including the Graphics Processing Unit‐based Monte Carlo dose calculation algorithm (GPUMCD) in the magnetic field, has rarely been evaluated.…”
Section: Introductionmentioning
confidence: 99%